Research Experience of Medical Students Collaborating in an International Peer Research Mentorship Program - Shah, Purva C.; Patel, Kajal; Suvarna, Akshata K.; Zulfiqar, Aysha; Ashok, Tejaswini; Siddiqui, Amna (International Journal of Medical Students, 2023)
Research and research teachings worldwide have undergone significant changes with advancements in the past decade. From students actively seeking research opportunities to participating in research workshops, it has given rise to a new era of mentor-mentee programs. The peer research mentorship program (PRMP) conducted by International Society for Chronic Illnesses (ISCI) facilitates a global collaboration that not only improves the quality of research but also encourages interpersonal relationships and incorporates expertise from different fields. In this article, medical students and early graduates share their experience of participating in a cross-country peer-to-peer mentorship and comment on their learnings and observations. This is an experience report of mentors and mentees in the ISCI sponsored PRMP. Mentees learned a lot about metabolic syndrome, alternative medicine, and narrative reviews and the mentor became more confident in her scientific writing skills, leadership qualities while also gaining in-depth knowledge about the integrative management of Metabolic Syndrome.